2010
DOI: 10.1007/s10047-010-0529-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and limitations of plasmapheresis in renal diseases: an evidence-based approach

Abstract: In use for over 50 years, the rationale for plasmapheresis remains based largely on case series and retrospective studies. Recently, results from several randomized controlled trials, meta-analyses, and prospective studies have shown plasmapheresis may be of benefit in various renal diseases, and have provided insights into more rational use of this therapy. A multicenter trial by the European Vasculitis Study Group has shown it is the preferred additional form of therapy for patients with anti-neutrophil cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 196 publications
0
7
0
3
Order By: Relevance
“…Official guidelines are published and updated regularly to guide clinicians with regards to initiation, continuation, and discontinuation of TPE . There is a specific group of patients with specific disease entities which require both TPE and HD during the course of treatment, thereby making simultaneous treatment an attractive option.…”
Section: Discussionmentioning
confidence: 99%
“…Official guidelines are published and updated regularly to guide clinicians with regards to initiation, continuation, and discontinuation of TPE . There is a specific group of patients with specific disease entities which require both TPE and HD during the course of treatment, thereby making simultaneous treatment an attractive option.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, results from several randomized controlled trials (RCTs), meta-analyses, and prospective studies have shown plasmapheresis may be of benefit in a variety of renal diseases, and have provided some insight into more rational use of this therapy, although many of the guidelines are still not based on results from RCTs [51].…”
Section: Apheresismentioning
confidence: 99%
“…Therapeutic plasma exchange (TPE) is a treatment modality to remove cir culating pathologic substances from the plasma and replace them with a sub stitution fluid (e.g., albumin or plasma) 1,2) . TPE has been applied in various dis eases such as neurological diseases (e.g., myasthenia gravis, GuillainBarré syndrome), hematological disorders (e.g., thrombotic thrombocytopenic pur pura, hemolytic uremic syndrome), metabolic disorders (e.g., inborn errors of metabolism, homozygous familial hypercholesterolemia), and kidney dis eases (e.g., the renal transplant candidate, antibody mediated renal allograft rejection, recurrent focal segmental glomerulosclerosis (FSGS) after renal transplantation, antineutrophil cytoplasmic antibodies and antiglomerular basement membrane antibodyassociated rapidly progres sing glomerulonephritis, and atypical hemolytic uremic syndrome (aHUS)) 3) .…”
Section: Introductionmentioning
confidence: 99%